IMPLEMENTASI METODE SMART DALAM PEMILIHAN ALAT KONTRASEPSI PADA PASANGAN USIA SUBUR STUDI KASUS : PUSKESMAS KOTA DATAR - Rahmawati, Rahmawati; Syari, Milli Alfhi; Saragih, Rusmin (Journal of Mathematics and Technology (MATECH), 2024)
This research implements the SMART (Specific, Measurable, Achievable, Relevant, and Time-bound) Method in the selection of contraceptives for couples of reproductive age at the Kota Datar Health Center. The aim is to assist couples in making informed decisions by ensuring that their contraceptive choices are specific, measurable, achievable, relevant, and time-bound. The study's findings are expected to help couples make smarter decisions regarding contraceptive methods that suit their needs.